Preparation of bacterial cellulose film from rotten fruits for mulching film application - Nattapong PINPRU; Varol INTASANTA; Thitirat CHAROONSUK; Supharada KHAISAAT; Oubonwan SAWANAKARN; Naratip VITTAYAKORN; Somsak WORAMONGKOLCHAI (My University, 2022)
This research aims to reduce production capital costs and added value to natural products. The bio-mulching film was prepared by bacterial cellulose (BC) “Acetobacter xylinum”, extracted from three rotten fruits, grape, coconut, and pineapple under standard tests in the laboratory. The analysis from the FTIR technique confirmed to cellulose molecular vibration of BC films. XRD pattern was matched to structure crystallinity of JCPDS standard file which possessed a high percentage of crystallinity. The SEM micrographs were also revealed the 3D nanofiber network structure. The absorption capability of BC films could highly hold water in its structure. In addition, the mechanical properties of BC films came from rotten coconut, given the highest tensile strength (7.2 ± 1.1 MPa) according to nano-fiber symmetric with its dense structure. Nevertheless, the soil burial testing emphasized BC films could reduce soil temperature and increase moisture content in the soil as well. The biodegradation rate of BC films in 30 days was moderately fair. The BC film from rotten coconut had the slowest biodegradation rate (approximately 22.3 4.2%), applicable to biodegradable mulching film.
Keywords: Bacterial Cellulose; Husk; Advanced Cellulose Research Studies